Gestão de portfólio de produtos: práticas adotadas por uma empresa de base tecnológica de médio porte localizada na cidade de São Carlos, SP - Burin Neto, Fabio; Barbalho, Sanderson Cesar Macêdo; Silva, Sergio Luis da; Jugend, Daniel [UNESP] (My University, 2013)
In the context of the product development process (PDP), portfolio management plays an important role by determing the set of products that a company uses to compete. Due to its characteristics, performing continuous technological forecasting activities for developing and transferring technologies to their products through the PDP, this tends to make portfolio management a complex activity for products at these companies. This paper’s objective was to identify practices for product portfolio management in a medium-sized technology-based firm located in São Carlos, SP. Qualitative research was used and it was operationalized through a case study. Among the main results, it was noted that decisions on product portfolio depend mainly on the perception of senior management and the financial analyzes constitute the main method used for supporting the decision.

No contexto do processo de desenvolvimento de produtos (PDP), a gestão de portfólio cumpre importante papel ao determinar o conjunto de produtos que uma empresa utiliza para competir no mercado. Por realizarem contínuas atividades de previsão tecnológica para o desenvolvimento e transferência de tecnologias aos seus produtos ao longo do PDP, a gestão de portfólio é atividade complexa, especialmente entre as empresas de base tecnológica. Este artigo tem o objetivo de analisar as práticas de gestão de portólio de produtos em uma empresa de base tecnológica de médio porte localizada na cidade de São Carlos, SP. Empregou-se o procedimento qualitativo de pesquisa, operacionalizado por meio de estudo de caso. Dentre os principais resultados, notou-se que as decisões em portfólio de produtos dependem, sobretudo, da percepção da alta administração e que as análises financeiras constituem-se no principal método de apoio à decisão utilizado.
Keywords: Product development process; Management of product portfolios; Technology-based companies; Processo de desenvolvimento de produtos; Gestão de portfólio; Empresas de base tecnológica